Peculiarities of the condition of vascular platelic hemostasis in diabetic retinopathy and diabetic nephropathy in rats - I. I. Hrytsan; I. V. Savytskyi; N. I. Preys; V. M. Sarakhan (Kazimierz Wielki University, 2020)
The article presents experimental data on the study of changes in vascular platelet hemostasis in rats with experimental DR and DN on the background of type 2 diabetes. It is established that microcirculatory complications of type 2 diabetes are characterized by a decrease in platelet count, increased aggregation capacity. In the study of induced platelet aggregation, the polarity of the results of the study was proved, which indicates the dependence of complications on the functional state of vascular platelet hemostasis, primarily due to stimulated, depleted platelets and the corresponding number of intact platelets. More pronounced changes in vascular-platelet hemostasis on the background of type 2 diabetes in rats with DN compared with the group of animals that reproduced DR.